A critical appraisal of the parol evidence rule in contract law - Shair Mohamed, Mohd. Akram; Ali Mohamed, Ashgar Ali (International Organisation Centre of Academic Research, 2014)
Under the common law the 'hallowed principle' in contract law is that once the parties have reduced their agreement into a written form, in the event of a dispute between them as to the written terms of the contract,they are prohibited from adducing extrinsic evidence to add to, subtract from, vary or contradict the written terms. The strict application of the rule was found to have caused hardship and worked unfairly to the parties. To mitigate the rigour of the rule, the judiciary created exception to the rule, whereby extrinsic evidence was allowed to be admitted. In time, the exceptions became so numerous as to virtually emasculate the 'hallowed' rule. To allay this uncertain state of affairs, law commission were set up in the United Kingdom, Canada, India and Singapore to reconsider the status of the rule. Some suggested a slight modification of the rule while the Law Commission in Ontario suggested a total abolition of the rule. This paper proposes to look at the nature of the 'parol evidence rule', numerous exceptions to it, the merits and demerits of the proposals for reform especially in the mother of common law England, Canada, India, Singapore and Malaysia.